42-48v=-54

Simple and best practice solution for 42-48v=-54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42-48v=-54 equation:


Simplifying
42 + -48v = -54

Solving
42 + -48v = -54

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + -48v = -54 + -42

Combine like terms: 42 + -42 = 0
0 + -48v = -54 + -42
-48v = -54 + -42

Combine like terms: -54 + -42 = -96
-48v = -96

Divide each side by '-48'.
v = 2

Simplifying
v = 2

See similar equations:

| 9=8-x/4 | | 4(2a)-a= | | 4w-5=12w-4 | | (4x^2-1)(6x^2-9)= | | 5(d+5)+2d=-13-8d | | 1/3x-8=4/9x | | 20=a/9 | | 26=13/v | | -7(3a-2)+4(5a+5)= | | 10=6+(1+3m)-2(2+10m) | | X-y=110 | | 7x-3x(x+1)= | | 6+2[3j-2]=4[1+j] | | 1/y-1/2=4 | | 6(z/2-5)=36 | | q=10000-125p | | 12x^2-121/12=0 | | 12=m/5 | | X+y=280 | | 5.5=-1.5+x | | 2.3+n+1.4=0 | | x-86=135 | | -2(-5v+5)=5[2v+3(v+1)] | | Y=x^2-10x+45 | | 3(4x-3)+8x=68 | | 14xy-4xy=o | | -7=-17+x | | -5n-5(-7-2n)= | | E=0.14x^2+7.8x+540 | | -10(t-6)+116-16=108 | | 5x^9/8-15=0 | | 3600+x^2+144=x^2 |

Equations solver categories